Internet of things technologies for healthcare : third International Conference, HealthyIoT 2016, Västerås, Sweden, October 18-19, 2016, revised selected papers /: third International Conference, HealthyIoT 2016, Västerås, Sweden, October 18-19, 2016, revised selected papers. (2016) - Unknown
No abstract available